Acetylcholinesterase (ace‑1R) target site mutation G119S and resistance to carbamates in Anopheles gambiae (sensu lato) populations from Mali - Keïta, M.; Kané, F.; Thiero, O.; Traoré, B.; Zeukeng, F.; Sodio, A.B.; Traoré, S.F.; Djouaka, R.F.; Doumbia, S.; Sogoba, N. (Springer, 2020)
Background The long-lasting insecticidal nets (LLINs) and indoor residual spraying of insecticide (IRS) are major malaria vector control strategies in Mali. The success of control strategies depends on a better understanding of the status of malaria vectors with respect to the insecticides used. In this study we evaluate the level of resistance of Anopheles gambiae (sensu lato) to bendiocarb and the molecular mechanism that underlies it.